Edukasi Penggunaan Mikroba Selulolitik dalam Pengelolaan Limbah Ternak Sapi Perah di Desa Jabung Kabupaten Magetan - Pujiati, Pujiati; Dewi, Nurul Kusuma; Primiani, Cicilia (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the knowledge and understanding of the Mulyo Livestock Farmer Group in Jabung Village, Panekan District, Magetan Regency, regarding livestock waste management, which has not been properly implemented as waste is still being disposed of directly onto land adjacent to the river. The activity was carried out by providing education to dairy farmers on managing cattle manure into biogas using cellulolytic microbial optimizers. The implementation methods included: (1) survey/observation, (2) socialization/counseling, (3) monitoring, and (4) evaluation. Evaluation instruments consisted of assessment sheets and evaluation rubrics, while the results were analyzed through a Focus Group Discussion (FGD) to formulate a Follow-Up Action Plan (RTL) as the foundation for program sustainability. The results of this activity were: (1) a 100% increase in farmers’ knowledge regarding the importance and use of cellulolytic microbes in the bioconversion of agricultural and livestock waste; (2) a 76% improvement in farmers’ understanding of processing livestock waste into organic fertilizer and biogas; and (3) 94% of dairy farmers expressed willingness to produce microbial cultures independently to support the management of agricultural and livestock waste.